SEARCH FOR NEW NATURAL BIOSTIMULANTS AS THE BASIS OF BIOLOGICAL PRODUCTS FOR THE AGRICULTURAL SECTOR OF THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
A search was carried out for natural plant growth stimulants that simultaneouslyhave the properties of biopesticides. The experiment was carried out with isolates of microfloraisolated from various natural objects of the Kyrgyz Republic. Microflora strains isolated fromknown biological products were used as analogues. The stimulating and fungicidal properties ofthe isolates were tested on tomato seeds of the Minibel variety
Keywords: biostimulant, seeds, microflora, isolate.